Isothermal low-temperature oxidation behavior and kinetics of heavy oil - Wang, Ruofan; Zhao, Shuai; Sun, Xinge; Varfolomeev, Mikhail A.; Arkin, Kurbanjan; Yang, Fengxiang; Li, Haibo; Yuan, Chengdong (Petroleum science and technology, 2025)
In this study, the isothermal low-temperature oxidation (LTO) behavior of heavy oil was investigated by thermogravimetry combined with Fourier transform infrared spectroscopy. Furthermore, the kinetics analysis was conducted using general reaction rate models. The findings revealed that the LTO process of heavy oil could be divided into three distinct phases. The first phase, occurring between 50 and 100 °C, exhibited minimal mass loss and low absorbance of gas-phase products. In the second phase (100-250 °C) the produced gas predominantly consisted of saturated hydrocarbons and substances containing C=O groups. Lastly, in the third phase (250-300 °C), the signals of CO 2 and CO in the produced gas were significantly higher compared to the 50-250 °C range, indicating a shift in the oxidation mode of heavy oil from oxygenation to bond cleavage for temperatures higher than 250 °C. Kinetics analysis demonstrated an initial increase in reaction order and reaction rate from 50 to 100 °C, followed by a decrease from 100 to 250 °C, and a final increase from 250 to 300 °C. The negative activation energy observed in the second temperature interval was attributed to the negative temperature coefficient effect. This study provided valuable insights into the isothermal LTO reactions of heavy oil.